Archipelagic thinking in Merlinda Bobis’s Fish-Hair Woman corpus - Lee, Cheryl Julia (2023)
Following Édouard Glissant’s lead, archipelagic thinking challenges neocolonial epistemes and methodologies in imagining alternative relations among difference. It offers productive lines of thought in relation to Southeast Asia, which has historically been marginalized in the global imaginary. This article examines archipelagic thinking’s potential to rewrite this metageography through a reading of Merlinda Bobis’s narratives of the Fish-Hair Woman who trawls the river with her magical hair for victims of the 1980s Philippine communist counter-insurgency in the fictional town of Iraya, Philippines. Recuperating neglected geographies and histories through storytelling and deploying magical realism by way of deconstructing hegemonic epistemologies and ontologies, these narratives subvert centre–periphery dynamics by endowing the Philippines with cultural specificity and mythic significance while positioning it as a zone of cultural exchange and interconnectedness. Through them, Bobis articulates a model for negotiating relations among difference characterized by fluidity and respect, in alignment with Glissant’s relationality.